Evaluation of the isoflavones and estrogen effects on the rat adrenal. (3rd October 2017) - Marinho, Darci Souza; Calió, Michele Longoni; Santos, Miriam Aparecida; Ko, Gui Mi; Teixeira, Cristiane Paula; Carbonel, Adriana Ferraz; Lisbôa-Nascimento, Telma; Castro, Rodrigo Aquino; Simões, Ricardo Santos; Bertoncini, Clélia Rejane Antônio
Abstract: The aim of this study was to evaluate the morphometry and the gene expression of Ki-67, VEGF and caspase 3 and the stress oxidative in the adrenal gland of ovariectomized rats treated with estrogen or isoflavones. We used 15 Wistar rats ovariectomized treated with isoflavones or estrogen during 30 days. At the end of the treatment, the left adrenal gland was removed for subsequent histological studies and the right was used to evaluate gene expression of angiogenesis (VEGF-A), cell proliferation (Ki-67), apoptose (caspase 3 clivated) and oxidative stress. Treatment with estrogen showed a largest increase in the layers of the adrenal cortex than with isoflavones. These hypertrofic effects agree with higher expression elevation of Ki67 and VEGF, which did not occur with the caspase 3, indicating that isoflavones have great proliferative effect on the adrenal gland. Similar results were also observed on superoxide quantification show that isoflavone has a protective effect against oxidative stress. Our results indicate positively the trophic therapeutic potential of isoflavones has a protective effect and can contribute to the development of effective therapies to decrease the symptoms of menopause.